Applying Ã¢â‚¬Å“Make a MatchÃ¢â‚¬Â Model-based on Scientific Approach through Reward Education Game for Elementary School Students - Herwulan Irine Purnama (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
The main purpose of this study is to analyze how students learn by using the